2010
DOI: 10.2109/jcersj2.118.993
|View full text |Cite
|
Sign up to set email alerts
|

Chemical trend of Fermi-level shift in transition metal-doped TiO2 films

Abstract: The effect of doping a wide range of transition metals (TMs) including V, Cr, Mn, Fe, Co, and Ni into rutile TiO 2 films grown on Nb-doped TiO 2 (110) single-crystal substrates was investigated by photoemission spectroscopy and X-ray absorption spectroscopy. For all TM-doped TiO 2 films, the Ti 2p and O 1s core levels were similarly shifted to lower binding energies with increasing film thickness and the shifts were similarly saturated at a film thickness of about 15 nm. These peak shifts could be interpreted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…[6] When photoelectrons are accumulated at the TiO 2 surface, however, the band edge of TiO 2 can be slipped up to achieve more negative potential than Φ red , followed by the reductive dissolution of TiO 2 from Adv. [37,38] Because the reductive dissolution of TiO 2 likely leaves surface defects, such as partially reduced Ti 4+ sites or oxygen vacancies, particularly at sub-surface regions, these defects can serve as trap states, impeding the transport of photogenerated electrons. 2019, 9,1900179 Only for PTS did the binding energy of the Ti 4+ state gradually shift to a lower level (dotted lines).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] When photoelectrons are accumulated at the TiO 2 surface, however, the band edge of TiO 2 can be slipped up to achieve more negative potential than Φ red , followed by the reductive dissolution of TiO 2 from Adv. [37,38] Because the reductive dissolution of TiO 2 likely leaves surface defects, such as partially reduced Ti 4+ sites or oxygen vacancies, particularly at sub-surface regions, these defects can serve as trap states, impeding the transport of photogenerated electrons. 2019, 9,1900179 Only for PTS did the binding energy of the Ti 4+ state gradually shift to a lower level (dotted lines).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be assumed that the surface of TiO 2 is photoreduced into the Ti(OH) 3 compound followed by its dissolution into the electrolyte rather than remaining at the surface (i.e., reductive dissolution takes place). On the other hand, the binding energy shift toward lower energies can be explained by the lowered fermi level of TiO 2 , typically observed when additional trap states form within the bandgap . Because the reductive dissolution of TiO 2 likely leaves surface defects, such as partially reduced Ti 4+ sites or oxygen vacancies, particularly at sub‐surface regions, these defects can serve as trap states, impeding the transport of photogenerated electrons .…”
Section: Resultsmentioning
confidence: 99%
“…These studies were completed by photocurrent and electron spin resonance (ESR) measurements few years later . Surprisingly, to our knowledge, only a few other experimental studies have been reported on the systematic characterization of TM doping in this material. In parallel, plenty of first-principles insights have been collected on doped rutile TiO 2 . Formation energies and charge transition levels of intrinsic defects have been carefully detailed through the use of density functional theory. ,, However, authors often did not consider extrinsic dopants.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-doped TiO 2 materials have recently received a lot of attention [31][32][33]. In this perspective, we have considered two others interactions: (1) insertion when M is inserted between the two top-layers and (2) substitution/ insertion when M substitutes one surface penta-coordinated Ti that becomes inserted between the two top layers.…”
Section: Introductionmentioning
confidence: 99%